Characteristics of Islamic Boarding School Students: A Study of Educational Islamic Characteristics of Islamic Boarding School Students In Syaichona Moh. Cholil Islamic Boarding School Bangkalan - Mardi, Moh.; Syam, Nur; Khumaidah, Sofkhatin; Humaidi, Humaidi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
Islamic boarding schools in Indonesia have a significant role to play in producing a young generation with the character to achieve this nation's ideals. Education character will only be formed with support from various parties. Therefore, the role of schools, either formal or non-formal (Islamic boarding schools), is very decisive in achieving that goal. This study aims to describe the character of the Islamic boarding school students (santri) and the inculcation of Islamic morality in the santri who are in the wrong Islamic boarding school in Indonesia, namely the Syaichona Moh Islamic Boarding School. Cholil Bangkalan is part of the contribution of Islamic boarding schools in building a developed and civilized country. This research was conducted with a qualitative descriptive approach with data collection methods: interviews, observation, and documentation. The analysis of Miles and Huberman models found that planting Islamic characters applied in the cottage is integrated with the obligations, prohibitions, and sanctions for those who break the rules. Efforts to instil this character are applied in students' religious activities (ubudiyah), pesantren, and school programs. Then from the efforts to teach the Islamic personality, students are formed religious education which is built on the vision and mission of the pesantren and is strengthened by all shoulder cuttings in the boarding school environment.